The Role of Organizational Culture, Knowledge Management, and Employee Engagement on Turnover Intention - Veritia, Veritia; Moeins, Anoesyirwan; Sunaryo, Widodo (Eastasouth Institute, 2024)
Indonesia is the world's largest palm oil producer and exporter in international trade. Although working in this field is quite promising, there are still many employees who have the intention to change jobs. This study aims to look at the influence of organizational culture, knowledge management, and employee engagement on the intention to move. This type of research uses mixed methods. Mixed Methods is a research method that combines quantitative research and qualitative research. In this research method using a sequential explanatory combination, starting with using quantitative methods and then expanding with qualitative and comparing the average results of both. In this study using a linearity test which is used to determine the regression model of the independent variable on the dependent. The population contained in this study is an affordable population of 1960 companies and an affordable population of 321 employees from Palm Oil Company Group. The sample in this study was 179 employees. The results of this study are 1) Organizational culture has a negative effect on turnover intentions, 2) knowledge management has a negative effect on switching intentions, 3) employee engagement has a negative effect on switching intentions.